PENDAMPINGAN LITERASI GERAKAN MENUMBUHKAN MINAT BACA BAGI ANAK–ANAK LOKR DI DUSUN WAIPUTIH - Nanik Handayani; Nana Ronawan Rambe (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Children's reading ability is the basis for mastering various fields. PISA data 2018 shows that the literacy and numeracy abilities of Indonesian children tend to be stagnant and are ranked second from the bottom. To develop children's literacy and numeracy skills, appropriate strategies are needed so that children are interested and trained to develop reading, writing and understanding the information around them. This PKM aims to provide assistance as an effort to strengthen children's literacy. The method in this PKM is by applying the LOKR steps namely Literacy, Orientation, Collaboration and Reflection. The result of this activity is that at the literacy stage the child still has difficulty answering questions from the story that has been read, it is necessary to do repetition and reinforcement at the orientation stage students have started to find answers, the collaboration stage is carried out to stimulate children who are still considered low to understand the meaning of reading, at In the reflection stage, the child can find answers to questions. The conclusion of this activity is that children's literacy skills tend to be at the level of needing intervention and basic. Furthermore, habituation is needed so that children like to read and understand what they read. It was proven that at the third meeting in this PKM activity the children had increased their ability to read and understand the contents of their reading.